Implementasi Green Chemistry Dalam Pembelajaran Kimia: Literatur Review - Shorihatul Inayah; I Wayan Dasna; Habiddin Habiddin (Hydrogen: Jurnal Kependidikan Kimia, 2022)
Green chemistry in chemistry learning has been a central issue in chemistry education research the last ten years. The objectives of this literature review are: a) to map green chemistry research topics in chemistry learning the last ten years; b) to find out the opportunity for the implementation of Green chemistry in chemistry learning. The research method used is a systematic literature review of articles published in the scopus journal obtained from the Scopus database for the last 10 years (2011-2021). Article searches use titles, abstracts or keywords that meet logical conditions ("Green Chemistry") or ("Chemistry"). The population of this study was 200 articles published in the Scopus database and the sample used was 19 articles. The findings show that: a) the trend of the most topics discussing green chemistry in organic chemistry by 68% and green chemistry in environmental chemistry by 16%, b) green chemistry provides a very large opportunity in chemistry learning. Thus, it can be concluded that the implementation of green chemistry in chemistry learning is very important and needed in preventing environmental pollution.